2015
DOI: 10.1515/polyeng-2014-0312
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic acid)/polypropylene and compatibilized poly(lactic acid)/polypropylene blends prepared by a vane extruder: analysis of the mechanical properties, morphology and thermal behavior

Abstract: Poly(lactic acid)/polypropylene and compatibilized poly(lactic acid)/polypropylene blends prepared by a vane extruder: analysis of the mechanical properties, morphology and thermal behavior Abstract: Poly(lactic acid) (PLA)/polypropylene (PP) blends with different weight fractions were prepared by a novel vane extruder. The mechanical properties, morphology, crystallization behavior and thermal stability of the blends were investigated. The tensile strength, flexural strength and elongation at break decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Many studies have been done to overcome these disadvantages and expand the range of applications of PLA, including the mechanisms of toughening, copolymerization, formation of the spatial complex of PLA, the addition of nanoparticles and nucleating agents and blending with polymers [11,12,22]. Among all these approaches, polymer blending has been considered more due to the practicality of this method in making new materials with various and custom properties as well as its cost-effectiveness [23][24][25]. The use of blends is very common in industry, because blending is a low-cost method for combining the properties of blended components into single materials [23].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been done to overcome these disadvantages and expand the range of applications of PLA, including the mechanisms of toughening, copolymerization, formation of the spatial complex of PLA, the addition of nanoparticles and nucleating agents and blending with polymers [11,12,22]. Among all these approaches, polymer blending has been considered more due to the practicality of this method in making new materials with various and custom properties as well as its cost-effectiveness [23][24][25]. The use of blends is very common in industry, because blending is a low-cost method for combining the properties of blended components into single materials [23].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been done to overcome these disadvantages and expand the range of applications of PLA, including the mechanisms of toughening, copolymerization, formation of the spatial complex of PLA, the addition of nanoparticles and nucleating agents and blending with polymers [11,12,22]. Among all these approaches, polymer blending has been considered more due to the practicality of this method in making new materials with various and custom properties as well as its cost-effectiveness [23][24][25]. The use of blends is very common in industry, because blending is a low-cost method for combining the properties of blended components into single materials [23].…”
Section: Introductionmentioning
confidence: 99%
“…The use of blends is very common in industry, because blending is a low-cost method for combining the properties of blended components into single materials [23]. Blending PLA with engineering polymers is an effective way to overcome most of its limitations [24]. In recent years, there has been much research on PLA blends with engineering polymers such as polycarbonates [26], polymethyl methacrylate [27], polyesters [28] and polyamides (PAs) [7,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Choudary et al [11] revealed that the mechanical properties of PLA have improved significantly with PP in the matrix blends. In terms of thermal stability, Chen et al reported that PLA/PP blends improved as measured by thermogravimetric analysis (TGA) [12]. It is worth noting that PP is thermally stable as compared to PLA; for example, PP started to degrade at 418.8 °C, whereas PLA was 334.3 °C.…”
Section: ■ Introductionmentioning
confidence: 99%